2019
DOI: 10.3390/min9100587
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroxylation and Structural Distortion of Kaolinite as a High-Temperature Sorbent in the Furnace

Abstract: As a high-temperature sorbent, kaolinite undergoes the flash calcination process in the furnace resulting in the dehydroxylation and structural distortion, which are closely related to its heavy metal/alkali metal adsorption characteristics. We investigated the flash calcination of kaolinite by the experiments using a drop tube furnace and by the characterization of flash-calcined products using thermogravimetric-differential scanning calorimeter (TG-DSC), X-ray diffraction (XRD), Fourier Transform Infrared Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 41 publications
0
26
1
Order By: Relevance
“…To further confirm the water or hydroxyl species in the sorbents, FTIR analysis was conducted (these curves are shown in Figure S1) between 3000-4000 cm -1 where the parallel vibration frequency of hydrogen-oxygen bond occurs. All sorbents possessed the board flat peaks at 3420 cm -1 that represents hydrogen bonds indicating adsorbed or bound water, while raw kaolin had four noticeable hydroxyl peaks (connected with aluminium atoms) between 3600-3700 cm -1 (Cheng et al, 2019). The rehydroxylation reported in some studies was not observed in this study, which may be attributed to the lower pressure of hydrothermal in this study than that in the literature (Zemenová et al, 2014;Kloužková et al, 2013).…”
Section: The Properties Of Sorbentscontrasting
confidence: 50%
See 2 more Smart Citations
“…To further confirm the water or hydroxyl species in the sorbents, FTIR analysis was conducted (these curves are shown in Figure S1) between 3000-4000 cm -1 where the parallel vibration frequency of hydrogen-oxygen bond occurs. All sorbents possessed the board flat peaks at 3420 cm -1 that represents hydrogen bonds indicating adsorbed or bound water, while raw kaolin had four noticeable hydroxyl peaks (connected with aluminium atoms) between 3600-3700 cm -1 (Cheng et al, 2019). The rehydroxylation reported in some studies was not observed in this study, which may be attributed to the lower pressure of hydrothermal in this study than that in the literature (Zemenová et al, 2014;Kloužková et al, 2013).…”
Section: The Properties Of Sorbentscontrasting
confidence: 50%
“…The sharp peak of RK at 93 ppm represents Si 3 (connecting with three bridge oxygen atoms), and peaks of other minerals at 112 ppm represent Si 4 (connecting with four bridge oxygen atoms, which means all the four bonds of SiO4 group connects with another four SiO4 groups). The conversion from Si 3 of RK to Si 4 of MK was due to the dehydroxylation after calcination (Cheng et al, 2019). When comparing the curves between MK and modified sorbents, the pressured hydrothermal treatment seemed to increase the proportion of Si 3 as the curves were lifted on the right side.…”
Section: The Properties Of Sorbentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mullite has been synthesized using various methods, such as sol‐gel process, chemical syntheses, 13,14 co‐precipitation, 6,15 hydrothermal reaction, 16,17 flash combustion, 18–19 and chemical vapor deposition 20,21 . However, the production of high‐purity and high‐density mullite is still a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Other applications include window materials under harsh chemical conditions and mechanical stress at high temperatures. [10][11][12] Mullite has been synthesized using various methods, such as sol-gel process, chemical syntheses, 13,14 co-precipitation, 6,15 hydrothermal reaction, 16,17 flash combustion, [18][19] and chemical vapor deposition. 20,21 However,…”
mentioning
confidence: 99%